Ciliated Cells Express a Novel Pattern of Brain-Derived Neurotrophic Factor in Allergic Rhinitis - Fang L; Li CH; Zhang Q; Jiang TJ; Liu Y; Shi FP; Yu P; Yu L; Chen AP; Li T; Wan YZ; Shi L (Journal of Inflammation Research, 2023)
Li Fang,1,2 Chun-Hao Li,1,3 Qian Zhang,1,3 Tian-Jiao Jiang,1,3 Yuan Liu,1,2 Feng-Po Shi,1,3 Peng Yu,1,3 Liang Yu,1,3 Ai-Ping Chen,1,3 Tao Li,1,3 Yu-Zhu Wan,1,3 Li Shi1,3 1Department of Otolaryngology-Head and Neck Surgery, Shandong Provincial ENT Hospital, Shandong University, Jinan, Shandong, People’s Republic of China; 2Department of Otolaryngology Head & Neck Surgery, The Second People’s Hospital of Shenzhen, Shenzhen, Guangdong, People’s Republic of China; 3Department of Allergy, Shandong Second Provincial General Hospital, Jinan, Shandong, People’s Republic of ChinaCorrespondence: Tao Li; Yu-Zhu Wan, Department of Otolaryngology-Head and Neck Surgery, Shandong Provincial ENT Hospital, Shandong University, Duanxing West Road, Jinan, Shandong, 250033, People’s Republic of China, Tel +86 531 83086279 ; +86 531 83086280, Fax +86 531 87980304, Email ltwfmc@163.com; wanyuzhu001@126.comBackground: Mounting research indicates that brain-derived neurotrophic factor (BDNF), has great potential to increase neuro-hyperresponsiveness and airway resistance in airway allergic disease. The expression level of BDNF has been found to be notably elevated in lung/nasal lavage (NAL) fluid. However, the expression and position of BDNF in ciliated cells with allergic rhinitis remains unclear.Methods: Nasal mucosal cells were collected from patients with allergic rhinitis (AR) and mice which were performed under different allergen challenge time, then observed the expression and position of BDNF located in ciliated cells through the immunofluorescence staining. Nasal mucosa, serum and NAL fluid were collected also. The expression level of BDNF and IL-4/5/13 were detected by RT-PCR. The expressions of BDNF (in serum and NAL fluid), and total-IgE, ovalbumin sIgE (in serum) were detected by ELISA.Results: We found that MFI of BDNF in AR group’s ciliated cells was obviously lower than that in the control group, and a negative correlation was discovered between MFI and VAS score. It can be roughly divided into 5 patterns according to its location in the cytoplasm of ciliated cells. In the mouse model, the expressions of BDNF in serum and NAL fluid increased temporarily after allergen stimulation. The MFI of BDNF in ciliated cells displayed an initial increase followed by a subsequent decrease.Conclusion: Our study shows for the first time that, the expression and localization of BNDF were observed in the human nasal ciliated epithelial cells of allergic rhinitis, and the expression of level was less than the control group under the persistent state of allergy. BDNF expression in ciliated cells was transient increased after allergen stimulation and decreased to normal level after 24h in mouse model of allergic rhinitis. This might be the possible source of the transient increase of BNDF in serum and NAL fluid.Keywords: allergic rhinitis, BDNF, ciliated cell, NAL fluid